The Effect of Clickbait Headlines on Tribunnews.Com Online News Articles on the Reading Interest of Generation Z at FKI UMS - Putra, Dedy Pradana; Santoso, Budi (Riwayat: Educational Journal of History and Humanities, 2025)
development of digital technology has brought about significant changes in information consumption patterns, particularly among Generation Z. One phenomenon that has emerged is the use of clickbait headlines on online news portals as a strategy to capture readers' attention. This study aims to analyze the effect of clickbait headlines on Tribunnews.com on the reading interest of Generation Z students at the Faculty of Communication and Informatics, Universitas Muhammadiyah Surakarta. This study employs a quantitative approach using a survey method through a questionnaire distributed to 113 respondents. The sampling technique used is purposive sampling. The results indicate that the use of clickbait headlines has a significant influence on reading interest. The effects are not only an increase in curiosity but also lead to boredom or disappointment when the news content does not match the expectations set by the headline. These findings reinforce the Uses and Effects Theory, which states that media directly impacts readers' behavior, both in terms of increasing curiosity and causing boredom when the news content does not meet expectations.